Head Start, Household Instability, and Children's Externalizing Behavior Problems - Elise Chor (SAGE Publishing, 2024)
This study uses experimental and nationally representative Head Start Impact Study data to document the high incidence of multidomain household instability experienced by children eligible for the federal two-generation Head Start early childhood education program for low-income households. The study finds that household instability experienced during the preschool year is associated with higher levels of children's classroom inattentive/hyperactive, aggressive, and oppositional externalizing behavior problems at the end of kindergarten. This relationship is reduced and even eliminated by access to Head Start. Exploratory evidence suggests that Head Start's buffering effect may operate by reducing exposure to household instability-including the incidence of high levels of multidomain household instability and the use of parental care-as well as parent-child relationship conflict.